Synthesis of Cationic Polymer Coated Magnetite Nanoparticles Based on Poly(maleic anhydride-alt-1-octadecene) - Ong-art Thanetnit (Science Faculty of Chiang Mai University, 2019)
We describe here the synthesis of aqueous dispersed cationic polymer coated magnetite nanoparticles. The cationic polymer was synthesized by two-steps reaction: the ring-opening reaction of commercial poly(maleic anhydride-alt-1-octadecene) (PMAO) with 2-(2-aminoethoxy)ethanol and subsequently grafting with glycidyltrimethylammonium chloride to obtain modified poly(maleic anhydride-alt-1-octadecene) (MPMAO). The characterization of MPMAO was determined by ATR-FTIR, 1H and 13C-NMR spectroscopy. By emulsion evaporation method, the magnetite nanoparticles prepared by the chemical co-precipitation were encapsulated with MPMAO to form modified poly(maleic anhydride-alt-1-octadecene) coated magnetite nanoparticles (MPMAO-Fe3O4 NPs). The average hydrodynamic diameter and z-potential value of MPMAO-Fe3O4 NPs were analyzed by dynamic light scattering measurement which found to be 43.2 nm and +29.3 mV, respectively. Thermogravimetric analysis, transmission electron microscopy and vibrating sample magnetometry of MPMAO-Fe3O4 NPs were also studied.